Snare tip soft coagulation (STSC) after endoscopic mucosal resection (EMR) of large (> 20 mm) non pedunculated colorectal polyps: a systematic review and meta-analysis - Chandan, Saurabh; Facciorusso, Antonio; Ramai, Daryl; Deliwala, Smit; Mohan, Babu P.; Kassab, Lena L.; Draganov, Peter V.; Othman, Mohamed O.; Kochhar, Gursimran S. (Endoscopy International Open, 2022)
Background and study aims Endoscopic mucosal resection (EMR) of laterally spreading tumors (LSTs) > 20 mm in size can be challenging. Piecemeal EMR of these lesions results in high rates of adenoma recurrence at first surveillance colonoscopy (SC1). Snare tip soft coagulation (STSC) of post resection margins is a safe and effective technique to prevent adenoma recurrence. We conducted a systematic review and meta-analysis to evaluate the effectiveness and safety of this technique. Patients and methods Multiple databases were searched through April 2021 for studies that reported on outcomes of post EMR STSC for LSTs > 20 mm in size. Meta-analysis was performed to determine pooled odds of adenoma recurrence as well as pooled proportion of adverse events including intraprocedural and delayed bleeding as well as intraprocedural perforation events.Results Six studies including two randomized controlled trials (RCT) and four cohort studies with 2122 patients were included in the final analysis. Overall pooled odds of adenoma recurrence at SC1 with post EMR STSC compared to no STSC was 0.27 (95 % 0.18–0.42; I2 = 0 %), P < 0.001. Pooled rate of adenoma recurrence at SC1 in post EMR STSC cohort was 6 %. Rates of intraprocedural bleeding, delayed bleeding and intraprocedural perforation were 10.3 %, 6.5 % and 2 % respectively.Conclusions Our results show that thermal ablation of resection margins with STSC in LSTs > 20 mm is a safe and effective technique in reducing the incidence of adenoma recurrence.